Longer pre-hospital delay in first myocardial infarction among patients with diabetes: an analysis of 4266 patients in the Northern Sweden MONICA Study - Ängerud, Karin Hellström; Brulin, Christine; Näslund, Ulf; Eliasson, Mats (BioMed Central Ltd., 2013)
Abstract Background Reperfusion therapy reduces both morbidity and mortality in myocardial infarction, but the effectiveness depends on how fast the patient receives treatment. Despite the time-dependent effectiveness of reperfusion therapy, many patients with myocardial infarction have delays in seeking medical care. The aim of this study was to describe pre-hospital delay in a first myocardial infarction among men and women with and without diabetes and to describe the association between pre-hospital delay time and diabetes, sex, age, symptoms and size of residential area as a proxy for distance to hospital. Methods This population based study was based on data from 4266 people aged 25–74 years, with a first myocardial infarction registered in the Northern Sweden MONICA myocardial infarction registry between 2000 and 2008. Results The proportion of patients with delay times ≥ 2 h was 64% for patients with diabetes and 58% for patients without diabetes. There was no difference in delay time ≥ 2 h between men and women with diabetes. Diabetes, older age and living in a town or rural areas were factors associated with pre-hospital delay times ≥ 2 h. Atypical symptoms were not a predictor for pre-hospital delay times ≥ 2 h, OR 0.59 (0.47; 0.75). Conclusions A higher proportion of patients with diabetes have longer pre-hospital delay in myocardial infarction than patients without diabetes. There are no differences in pre-hospital delay between men and women with diabetes. The largest risk difference for pre-hospital delay ≥ 2 h is between women with and without diabetes. Diabetes, older age and living in a town or rural area are predictors for pre-hospital delay ≥ 2 h.